Christian Character Building for Police Cadets: A Community Service Program at SPN Polda Sulut, Manado - Yessy Kenny Jacob (Jurnal Penyuluhan dan Pemberdayaan Masyarakat, 2025)
This community service program aims to strengthen Christian character building among police cadets at SPN Polda Sulut, Manado, as an integral component of ethical formation and professional preparedness. Police cadets face complex moral challenges in contemporary law enforcement, including integrity dilemmas, public accountability, and pressure-filled decision-making environments. Grounded in Christian values such as integrity, discipline, compassion, responsibility, and servant leadership, the program was designed to support the development of moral character alongside technical and physical training.The program employed a participatory and educational approach through a series of structured activities, including character-building seminars, reflective Bible-based discussions, group counseling sessions, and interactive case studies relevant to policing contexts. These activities were facilitated by academics and religious practitioners and were aligned with the institutional vision of producing professional, ethical, and community-oriented police officers. The implementation stages consisted of needs assessment, program socialization, delivery of learning modules, and evaluation through observation and participant feedback.The results indicate positive outcomes in enhancing cadets’ awareness of ethical responsibilities, strengthening moral reasoning, and fostering attitudes of empathy, self-control, and accountability. Participants demonstrated improved understanding of how Christian values can be practically applied in law enforcement duties, particularly in serving the community with fairness and respect. Moreover, the program contributed to creating a supportive moral environment within the training institution.In conclusion, Christian character building through community service programs plays a significant role in shaping the moral foundation of police cadets. This initiative is expected to have a sustainable impact on personal integrity and professional conduct, thereby supporting the realization of trustworthy and humane policing in society.